Scaling Nurturing Care Interventions in the Health Sector: A Theory of Change Perspective - Muneera A. Rasheed (Frontiers Media S.A., 2022)
Nurturing care interventions postulated on strengthening caregiver-child relationships have proven to be effective for improving early childhood development outcomes in low- and middle-income countries. Hence, a scale-up of the interventions has been recommended with an emphasis on the health sector given the contact with families in the critical first 3 years of life. However, an effective scale-up of an integrated intervention through healthcare requires a theory of change approach elucidating pathways of sustainable change. From this viewpoint, I reflect on my experience of scaling the intervention in a private pediatric care setting. I realized that buy-in from the health sector required realization of benefits to include health outcomes framed as the potential to improve the quality of life and the process of recovery; sustainable behavior change required a culture that promoted nurturing care highlighting the role of leadership; subsequently improving the experience of frontline staff and at an individual level, this could be achieved through the provision of supportive supervision-rooted in a framework of compassion. The lessons learned are shared to be considered for future integration efforts.